Hyperthyroidism Recent Updates - Gelen, Volkan; Kükürt, Abdulsamed; Şengül, Emin (IntechOpen, 2023)
Hyperthyroidism is a condition caused by physiological, biological, and clinical findings that cause hypermetabolism as a result of the excessive elevation of thyroid hormones in the blood and the surrounding tissues under the influence of high levels of hormones. There is a general acceleration in metabolism. There are a wide variety of methods in the treatment of hyperthyroidism, such as antithyroid drugs, lithium carbonate, radioactive iodine, and dexamethasone. This comprehensive book, with contributions from various researchers on thyroid hormones and hyperthyroidism, offers a wide range of expert reviews on the release of thyroid hormones, their physiological effects, and the occurrence of hyperthyroidism as well as its types, effects, and treatment options.